2020
DOI: 10.1101/2020.04.04.025585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zebrafish macrophage developmental arrest underlies depletion of microglia and reveals Csf1r-independent metaphocytes

Abstract: 20Macrophages derive from multiple sources of hematopoietic progenitors. Most macrophages 21 require colony-stimulating factor 1 receptor (CSF1R), but some macrophages persist in the 22 absence of CSF1R. Here, we analyzed mpeg1:GFP-expressing macrophages in csf1r-23 deficient zebrafish and report that embryonic macrophages emerge followed by their 24 developmental arrest. In larvae, mpeg1+ cell numbers then increased showing two distinct 25 types in the skin: branched, putative Langerhans cells, and amoeboid c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 90 publications
(125 reference statements)
4
22
0
Order By: Relevance
“…3A,B, the complete loss of csf1r had no consequence on primitive macrophage ontogeny, as the number of mfap4 + cells in double mutants were similar to that of wildtype and single homozygous mutant embryos. This is consistent with our recent findings using the macrophage mpeg1:EGFP reporter line (Kuil et al, 2020). We next investigated the requirement of the different csf1r paralogs for the establishment of embryonic microglia, which differentiate in the brain parenchyma from primitive macrophages starting at 60 hpf (Ferrero et al, 2018; Herbomel et al, 2001).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…3A,B, the complete loss of csf1r had no consequence on primitive macrophage ontogeny, as the number of mfap4 + cells in double mutants were similar to that of wildtype and single homozygous mutant embryos. This is consistent with our recent findings using the macrophage mpeg1:EGFP reporter line (Kuil et al, 2020). We next investigated the requirement of the different csf1r paralogs for the establishment of embryonic microglia, which differentiate in the brain parenchyma from primitive macrophages starting at 60 hpf (Ferrero et al, 2018; Herbomel et al, 2001).…”
Section: Resultssupporting
confidence: 94%
“…Also, since the very few microglia present at 3 dpf in csf1ra or il34 -deficient embryos retain their proliferative capacity and can be increased by csf1a overexpression (Kuil et al, 2019; Oosterhof et al, 2018), it is tempting to speculate that csf1a and/or csf1b signalling through csf1rb triggers the proliferation of embryonic microglia in csf1ra mutants. In line with this interpretation, we recently showed that primitive macrophages in csf1r DM embryos, which lose interaction with all Csf1r ligands, exhibit both migration and proliferation defects (Kuil et al, 2020). Further investigation in zebrafish mutants combining Csf1 ligands and receptors knockout will be instrumental in testing this hypothesis.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…mpeg1.1 transgenics may therefore aid the characterization of these elusive cells. Our data also support the recent description of mpeg1.1 + epidermal metaphocytes (37,38), suggesting additional markers will be required to stratify these mpeg1.1 + csf1ra 2 populations in studies in the skin.…”
Section: Discussionsupporting
confidence: 89%
“…2C, 2F), this may suggest that mpeg1.1 is expressed in an additional csf1ra-negative population unique to the skin/fin. Indeed, the morphology of these cells is similar to that of the recently described nonmyeloid cell type, metaphocytes, which perform Ag processing functions in the skin of adult zebrafish (37,38). Therefore, our data suggest that two populations of mpeg1.1 + cells that do not express csf1ra exist in adult skin.…”
Section: Mpeg11 + Lymphoid Cells Are Present In Other Adult Tissuessupporting
confidence: 80%